The centipede family Anopsobiidae new to North America, with the description of a new genus and species and notes on the Henicopidae of North America and the Anopsobiidae of the Northern Hemisphere (Chilopoda, Lithobiomorpha) - Shear, William A. (Zootaxa, 2018)
Speleopsobius weaveri, n. gen., n. sp., is described from lava tubes in southern Idaho, USA. The new taxon, and species of the genera Buethobius Chamberlin, 1911 and its probable synonym Yobius Chamberlin, 1945, are members of the family Anopsobiidae, not previously reported from North America. All known species of Henicopidae and Anopsobiidae from North America north of México are listed and briefly noted, along with all known anopsobiids from the northern hemisphere. Anopsobiella dawidoffi Attems, 1938 (Vietnam) is likely not a member of the family Anopsobiidae.